Faktor Yang Mempengaruhi Rupture Perenium Pada Ibu Multipara di RSUD Sawerigading Palopo - Farida Farida; Arini Purnama Sari (Termometer: Jurnal Ilmiah Ilmu Kesehatan dan Kedokteran, 2023)
Perineal rupture is a birth canal wound that can occur spontaneously because the perineum is stiff, precipitate labor, wrong delivery leadership, no good cooperation with the mother during labor. Perineum rupture due to episotomy expands the birth canal due to large babies, premature, abnormal location and delivery with vacuum / forceps. This study used a cross-sectional research design, the population in this study were all birth mothers who experienced perineal rupture at Sawerigading Hospital, Palopo City, namely 318 mothers, sampling was carried out by purposive sampling with statistical chi-square test, so the total sample is 76 respondents. Data collection was carried out using a checklist sheet. In conclusion, there is no effect of shoulder dystocia on the incidence of perineal rupture in multiparous women, there is no effect of pressing on the incidence of perineal rupture and there is an effect of birth weight on the incidence of perineal rupture at Sawerigading Hospital, Palopo City in 2021.